(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This note reports for the first time a fish of the family Gempylidae from the Colombian waters, since four specimens of Promethichthys prometheus were collected nearby Santa Marta (Caribbean Sea).